Renal function: excretory system - Briffa, Jessica (Henry Stewart Talks, 2024)
Anatomy of the kidney, Overview of renal function, Glomerular filtration, Nephron function, Solute movement through the nephron, Composition of plasma, glomerular filtrate, and urine